2016
DOI: 10.3126/nje.v1i1.14735
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing sexual behaviour between tourists and tourism employees: A systematic review

Abstract: Abstract:Background: Increased travel abroad has a significant impact on the incidence and prevalence of Sexually Transmitted Infections (STIs). Previous reviews have focused on the knowledge, attitudes and behaviour of tourists and acquisition of STIs. Less is known about the impact on tourism operators in countries visited by tourists. The aim of this review is to ascertain factors influencing sexual behaviour between workers in the tourism industry and tourists; exploring the prevalence of sexual behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…With regards to preferred destinations, a meta-analysis conducted in 2018 showed that South/Central America and the Caribbean were more likely to receive tourists looking for casual sex [5]. Additionally, Thailand and Cuba also have a prevalent sex tourism industry [7,11]. One study found that 66% of Australian tourists to Thailand were planning on having a sexual encounter while there [11], while sex tourism in Cuba has been described as "integral to the Cuban experience" [12].…”
Section: Epidemiology Of Sex and Travelmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to preferred destinations, a meta-analysis conducted in 2018 showed that South/Central America and the Caribbean were more likely to receive tourists looking for casual sex [5]. Additionally, Thailand and Cuba also have a prevalent sex tourism industry [7,11]. One study found that 66% of Australian tourists to Thailand were planning on having a sexual encounter while there [11], while sex tourism in Cuba has been described as "integral to the Cuban experience" [12].…”
Section: Epidemiology Of Sex and Travelmentioning
confidence: 99%
“…Additionally, Thailand and Cuba also have a prevalent sex tourism industry [7,11]. One study found that 66% of Australian tourists to Thailand were planning on having a sexual encounter while there [11], while sex tourism in Cuba has been described as "integral to the Cuban experience" [12]. Traveller subtypes who were more likely to engage in sex included backpackers, travelling businessmen, those visiting friends and relatives (VFR), and those travelling specifically to solicit commercial sex workers [5].…”
Section: Epidemiology Of Sex and Travelmentioning
confidence: 99%
See 1 more Smart Citation